Dante's Gluttons Food and Society from the Convivio to the Comedy - Callegari, Danielle (Food Culture, Food History before 1900, 2022)
Dante's Gluttons: Food and Society from the Convivio to the Comedy explores how in his work medieval Italian poet Dante Alighieri (1265-1321) uses food to articulate, reinforce, criticize, and correct the social, political, and cultural values of his time. Combining medieval history, food studies, and literary criticism, Dante's Gluttons historicizes food and eating in Dante, beginning in his earliest collected poetry and arriving at the end of his major work. For Dante, the consumption of food is not a frivolity, but a crux of life in the most profound sense of the term, and gluttony is the abdication of civic and spiritual responsibility and a danger to the individual body and soul as well as to the collective. This book establishes how one of the world's preeminent authors uses the intimacy and universality of food as a touchstone, communicating through a gastronomic language rooted in the deeply human relationship with material sustenance